Prosument Behaviour In Brand Creating - Scheibe, Anna (Wyższa Szkoła Biznesu - National-Louis University in Nowy Sącz, 2012)
A brand remains a considerable source of the competitive advantage. One of the elements contributing to its power is image. The information revolution and globalization make it necessary to search for new means of differentiating brands. One of them is engaging consumers in the brand creation process. In light of the development of the Web 2.0, prosumers – active consumers functioning both as consumers and partly as producers – can have a meaningful influence on the image of brands. Their activities can entail both positive as well as negative effects.
Keywords: co-creations; brand; prosumer